Soil and Water Conservation in Arid and Semi-arid Areas: The Chinese Experience - Li, Xiao Yan (Annals of Arid Zone, 2016)
In China. soil erosion is a serious environmental problem and a major threat to the sustainability of agriculture and economic development. The total area subjected to soil erosion covers 3,670,000 km2, i.e., 38.2% of the total land area. For a long period of time, particularly since the founding of the People's Republic of China in 1949. the Chinese government has paid a great deal of attention to issues of soil and water conservation to promote economic development and better environmental management. This paper reviews soil and water conservation techniques adopted in arid and semi-arid regions of China and discusses the problems and perspectives for soil and water conservation strategies. The effective measures for wind erosion cDntrol include vegetative, engineering and chemical methods as well as land management practices, and measures for water erosion include transform topography, tillage and crop rotation management, mulching and rainwater harvesting system. Success in soil and water conservation often requires a combination of various measures, and it needs to be integrated within a comprehensive agricultural management system. In order to gain the potential ecological and economic benefits from soil and water conservation, policy and funding support are also necessary. In addition, further research is needed to assess the ecological, social and economic impacts of soil and water conservation system from a plurality of perspectives.